A chromatography-free isolation of rohitukine from leaves of Dysoxylum binectariferum: Evaluation for in vitro cytotoxicity, Cdk inhibition and physicochemical properties. Issue 15 (1st August 2016) - Kumar, Vikas; Guru, Santosh K.; Jain, Shreyans K.; Joshi, Prashant; Gandhi, Sumit G.; Bharate, Sandip B.; Bhushan, Shashi; Bharate, Sonali S.; Vishwakarma, Ram A.
Graphical abstract: Abstract: Rohitukine is a chromone alkaloid isolated from an Indian medicinal plant Dysoxylum binectariferum . This natural product has led to the discovery of two clinical candidates (flavopiridol and P276-00) for the treatment of cancer. Herein, for the first time we report an efficient protocol for isolation and purification of this precious natural product in a bulk-quantity from leaves (a renewable source) of D. binectariferum (>98% purity) without use of chromatography or any acid–base treatment. Despite of the fact that this scaffold has reached up to clinical stage, particularly for leukemia; however the antileukemic activity of a parent natural product has never been investigated. Furthermore, rohitukine has never been studied for cyclin-dependent kinase (Cdk) inhibition, kinase profiling and for its experimental physicochemical properties. Thus, herein, we report in vitro cytotoxicity of rohitukine in a panel of 20 cancer cell lines (including leukemia, pancreatic, prostate, breast and CNS) and 2 normal cell lines; kinase profiling, Cdk2/9 inhibition, and physicochemical properties (solubility and stability in biological medias, p K a, Log  P, Log  D ). In cytotoxicity screening, rohitukine displayed promising activity in HL-60 and Molt-4 (leukemia) cell lines with GI50 of 10 and 12 μM, respectively. It showed inhibition of Cdk2/A and Cdk9/T1 with IC50 values of 7.3 and 0.3 μM, respectively. The key interactions of rohitukine with Cdk9 was also studied by molecular modeling. Rohitukine was found to be highly water soluble ( S water  = 10.3 mg/mL) and its Log  P value was −0.55. The ionization constant of rohitukine was found to be 5.83. Rohitukine was stable in various biological media's including rat plasma. The data presented herein will help in designing better anticancer agents in future.